KEPUASAN KERJA MEMEDIASI BERBAGI PENGETAHUAN DAN KESEIMBANGAN KERJA TERHADAP PERILAKU KERJA INOVATIF PEGAWAI DINAS KESEHATAN PROVINSI BENGKULU - Ella Febiola; Praningrum Praningrum (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine whether job satisfaction mediates knowledge sharing and work balance on the innovative work behavior of employees of the Bengkulu Provincial Health Office. This research method is a quantitative method with data collection techniques carried out by distributing questionnaires using a Likert scale. In the validity test results for 40 questionnaire question items are declared valid, where the Correlation value is above the R-table or more than 0.1166 and significant below 0.05. For the reliability test, the questionnaire that has been distributed is reliable because the Cronbach's Alpha value is> 0.60. The value of the knowledge sharing variable is 0.783> 0.60, the work balance variable is 0.985> 0.60, innovative work behavior is 0.989> 0.60 and for job satisfaction is 0.923> 060. The normalization test that the asymp.sig value is 0.246 which means greater than 0.05 so it can be concluded that the data is normal distribution. Multiple linear regression model (1) for all variables is declared significant because all values are greater than 0.05. Multiple linear regression model (2) for all variables is valid because the value of R2 or R square contained in the summry model table is 0.847, this shows that the contribution of X1, X2 and Y to M is 84.7%.